New insights into prehistoric agriculture of northern Iberia from the analysis of starch grains embedded in dental calculus - González-Rabanal, Borja; Marín-Arroyo, Ana B.; Carmona-Ballestero, Eduardo; Cuenca-Solana, David; Gutiérrez-Zugasti, Igor; Martín-Merino, Miguel Ángel; Ortega-Martínez, Ana Isabel; Straus, Lawrence G.; Vega-Maeso, Cristina; González Morales, Manuel R.; Cristiani, Emanuela (Frontiers in Ecology and Evolution, 2025)
IntroductionResearch on the origin and spread of agriculture in northern Atlantic Iberia remains partially limited because archaeobotanical data are scarce due to old excavations or preservation biases.MethodsIn this paper, we present starch grain analyses of dental calculus of 18 individuals from 10 sites dated to the 4th/2nd millennium cal BCResultsThis research supports the development of extensive and stable agriculture, based on the cultivation of wheat and barley species, from the Neolithic to the Bronze Age, when millets were introduced, marking the primary shift of the Cantabrian farming economy and revealing a more diversified and mixed agriculture thereafter. In parallel, legumes were less cultivated since the Neolithic and probably used as a secondary plant resource by the Cantabrian communities.DiscussionOur results have also allowed us to corroborate previous regional archaeobotanical and isotopic data and enhance the archaeological evidence of plant consumption during Late Prehistory, establishing a diachronic multiapproach to the development of agricultural practices in this area and providing a methodological framework for future studies.